(15+7).3-24
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
a, = 15 x (3+7) + 15 = 15 x 10 + 15 = 150 + 15 = 165
b, = 24 x 18 - 24 x 8 + 24 = 24 x (18-8) + 24 = 24 x 10 + 24 = 240 + 24 = 264
k mk nha
a,15*3+15*7+15
=15*(3+7)
=15*10
=150
b,24*18-24*7
=24*(18-7)
=24*11
=264
tk cho mk nha^-^
Ta có: \(A=\dfrac{-5}{7}:\left(25-24\dfrac{4}{7}\right)+15\dfrac{1}{3}\cdot\dfrac{-1}{23}\)
\(=\dfrac{-5}{7}:\left(25-\dfrac{172}{7}\right)+\dfrac{46}{5}\cdot\dfrac{-1}{23}\)
\(=\dfrac{-5}{7}\cdot\dfrac{7}{3}+\dfrac{-2}{5}\)
\(=\dfrac{-5}{3}+\dfrac{-2}{5}\)
\(=\dfrac{-31}{15}\)
d=43/37d=43/37 × 23/15−43/3723/15−43/37 × 8/15+31/378/15+31/37
=43/37=43/37 x 23/15+43/3723/15+43/37 x (−8/15)+31/37(−8/15)+31/37
=43/37(23/15−8/15)+31/37=43/37(23/15−8/15)+31/37
=43/37.1+31/37=43/37.1+31/37
=2=2
E=−5/24E=−5/24 × 9/11−5/249/11−5/24 × 2/11+7/122/11+7/12
=−5/24(9/11+2/11)+7/12=−5/24(9/11+2/11)+7/12
=−5/24.1+7/12=−5/24.1+7/12
=3/8=3/8
a)3/7–−11/14−7/3×6/7a)3/7–−11/14−7/3×6/7
=3/7−−11/14−2=3/7−−11/14−2
=3/7+11/14−2=3/7+11/14−2
=−11/14=−11/14
b)6/5:3/2+−2/3×9/14b)6/5:3/2+−2/3×9/14
=4/5−3/7=4/5−3/7
=13/35
d=43/37d=43/37 × 23/15−43/3723/15−43/37 × 8/15+31/378/15+31/37
=43/37=43/37 x 23/15+43/3723/15+43/37 x (−8/15)+31/37(−8/15)+31/37
=43/37(23/15−8/15)+31/37=43/37(23/15−8/15)+31/37
=43/37.1+31/37=43/37.1+31/37
=2=2
E=−5/24E=−5/24 × 9/11−5/249/11−5/24 × 2/11+7/122/11+7/12
=−5/24(9/11+2/11)+7/12=−5/24(9/11+2/11)+7/12
=−5/24.1+7/12=−5/24.1+7/12
=3/8=3/8
a)3/7–−11/14−7/3×6/7a)3/7–−11/14−7/3×6/7
=3/7−−11/14−2=3/7−−11/14−2
=3/7+11/14−2=3/7+11/14−2
=−11/14=−11/14
b)6/5:3/2+−2/3×9/14b)6/5:3/2+−2/3×9/14
=4/5−3/7=4/5−3/7
=13/35
2/3 + 7/1 = 2/3 + 7 = 2/3 + 21/3 = 23/3
25/48 + 11/24 = 25/48 + 22/48 = 47/48
5/7 + 3/8 = 40/56 + 21/56 = 61/56
15/24 + 12/6 = 5/8 + 2 = 5/8 + 16/8 = 21/8
5/6 + 4/3 = 5/6 + 8/6 = 13/6
3/8 + 7/12 = 9/24 + 14/24 = 23/24
câu a :
\(\dfrac{-8}{24}+\dfrac{-4}{12}=\dfrac{-1}{3}+\dfrac{-1}{3}=\dfrac{-2}{3}\)
câu b :
\(\dfrac{-20}{35}+\dfrac{16}{24}=\dfrac{-4}{7}+\dfrac{2}{3}=\dfrac{2}{21}\)
câu c :
\(\dfrac{-3}{9}+\dfrac{-6}{15}=\dfrac{-1}{3}+\dfrac{-2}{5}=\dfrac{-11}{15}\)
câu d :
\(\dfrac{3}{13}-\dfrac{4}{10}=\dfrac{3}{13}-\dfrac{2}{5}=\dfrac{-11}{65}\)
câu e :
\(\dfrac{5}{17}-\dfrac{9}{15}=\dfrac{5}{17}-\dfrac{3}{5}=\dfrac{-26}{85}\)
câu g :
\(\dfrac{9}{18}-\dfrac{6}{15}+\dfrac{3}{-9}=\dfrac{9}{18}-\dfrac{6}{15}+\dfrac{-3}{9}\\ =\dfrac{1}{2}-\dfrac{2}{5}+\dfrac{-1}{3}=\dfrac{-7}{30}\)
câu h :
\(\dfrac{5}{4}-\dfrac{1}{2}+\dfrac{-7}{8}=\dfrac{10}{8}-\dfrac{4}{8}+\dfrac{-7}{8}=\dfrac{-1}{8}\)
\(\dfrac{15}{24}-\dfrac{3}{8}-\dfrac{1}{6}=\dfrac{5}{8}-\dfrac{3}{8}-\dfrac{1}{6}=\dfrac{1}{4}-\dfrac{1}{6}=\dfrac{1}{12}\)
\(\dfrac{7}{13}\cdot\dfrac{5}{24}\cdot\dfrac{39}{75}=\dfrac{39}{13}\cdot\dfrac{5}{75}\cdot\dfrac{7}{24}=3\cdot\dfrac{1}{15}\cdot\dfrac{7}{24}=\dfrac{35}{24}\)
TL :
( 15 + 7 ) . 3 - 24
= 22 . 3 - 24
= 66 - 24
= 42
_HT_